2019
DOI: 10.21608/jpp.2019.36267
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Grain Priming and its Duration on Wheat Germination and Seedling Growth

Abstract: This study was designed to investigate the effect of different grain priming methods on germination and seedling vigour of wheat cultivar (Gemmiza 9) was performed. Grains were primed for 8, 16 and 24 hours in 13 priming media (water, polyethylene glycol 6000 at 2.5, 5, 7.5 %; CaCl 2 at 250, 500, 1000 ppm; ascorbic acid (AsA) at 25, 50, 100 ppm; salicylic acid (SA) at 50, 100, 150 ppm) beside dry grain as a control. In general, it was observed that a priming duration of 24 hr gave the highest values of all dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…But Aras genotype shows highest accumulated dry matter; 0.28 g due to hydro priming method (Figure 3). These results corroborate with those of Yücel and Heybet (2016) and Mohamed et al (2019) for Salicylic acid. SA increases the level of cell division of seedlings and roots, which increased seedling growth and higher germination indices as compared to control plants (Dolatabadian et al, 2009).…”
Section: Effect Of Seed Priming Techniques On Germination Conductancesupporting
confidence: 90%
See 1 more Smart Citation
“…But Aras genotype shows highest accumulated dry matter; 0.28 g due to hydro priming method (Figure 3). These results corroborate with those of Yücel and Heybet (2016) and Mohamed et al (2019) for Salicylic acid. SA increases the level of cell division of seedlings and roots, which increased seedling growth and higher germination indices as compared to control plants (Dolatabadian et al, 2009).…”
Section: Effect Of Seed Priming Techniques On Germination Conductancesupporting
confidence: 90%
“…Salicylic acid priming in fennel seeds also showed better germination under low water potential (Farahbakhsh, 2012). As well as Mohamed et al (2019) reported that seed priming with salicylic acid (100 ppm) enhanced seedling vigor by increased photosynthesis and biochemical processes. Imran et al (2014) claimed that Priming with 2% A. vera gel was most effective in boosting up germination rate and succeeding seedling growth under chilling conditions.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, (Haidar and Saba, 2017) mentioned that treating seeds with salicylic before planting helps to the seed imbibition, which provides additional storage for the embryo. The stimulating of wheat seeds with salicylic acid at a concentration of 50 mg.L -1 has led to an increase in germination percentage, seedlings freshness, and dry weight compared to dry non-activated seeds (Mohamed et al, 2019). (Moghanibashi et al, 2012) stated that priming sunflower seeds with water has improved the performance of the crop seeds and reduced the average germination time, and indicated that priming sunflower seeds in water for 24 hours led to give the highest values of the plumule and radicle weight, and their length.…”
Section: Introductionmentioning
confidence: 99%
“…The test weight of VL 829 primed for 24 hours with normal water was recorded significantly higher than the VL 892.The priming for 24 hour with normal water gave higher yield than priming for 12 hours and was statistically on par. Mohamed et al, 2019 also reported that 24 hours priming duration is better than other duration in wheat. Ali and Sajed, 2009 also reported similar results in case of chickpea.…”
Section: Yield Attributes and Yieldmentioning
confidence: 92%